The Influence of Workload and Work Stress on Employee Performance at PT Pos Indonesia (Persero) Kantor Sentral Pengolahan Pos Semarang - Winda Martha Prasetyani; Rustono - Rustono; Suwardi - Suwardi (Politeknik Negeri Semarang, 2022)
Human resources are the main role in achieving corporate objective. This study aims to analyse the workload and work stress on Employee Performance at PT Pos Indonesia (Persero) Kantor Sentral Pengolahan Pos Semarang. This research is a quantitative study with 38 respondents. The sampling technique is saturated sampling technique. The data-collection technique used are questionnaires, interviews, and literature review. The analysis technique used was multiple linear regression. The result shows that partially workload is negative and insignificant influence on employee performance, and work stress is positive and significant influence on employee performance. Simultaneuously workload and work stress have significant influence on employee performance. The influence of workload and work stress on employee performance is shown by Adjusted R Square value 0,115 (11,5%) and the remaining 88,5% are influenced by other variables that are not studied in this research